2017
DOI: 10.1097/iop.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost 3D Printing Orbital Implant Templates in Secondary Orbital Reconstructions

Abstract: The technique and cases presented demonstrate 1) the feasibility and accessibility of low-cost, independent use of 3D printing technology to fashion patient-specific implants in orbital reconstructions, 2) the ability to apply this technology to the surgeon's preference of any routinely implantable material, and 3) the utility of this technique in complex, secondary reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…However, considering that individual patients have different orbital morphologies, these earlier method were limited by being unable to take full advantage of 3D printing technology to produce fully customized implants. Also, there is technology available for directly printing a suitable biocompatible material for implantation into the orbit, although this is largely limited to titanium [4]. Pure titanium implants are usually far from being ideal for orbital wall reconstruction for the most commonly occurring simple one-wall blowout fractures and are associated with complications of orbital adherence syndrome [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, considering that individual patients have different orbital morphologies, these earlier method were limited by being unable to take full advantage of 3D printing technology to produce fully customized implants. Also, there is technology available for directly printing a suitable biocompatible material for implantation into the orbit, although this is largely limited to titanium [4]. Pure titanium implants are usually far from being ideal for orbital wall reconstruction for the most commonly occurring simple one-wall blowout fractures and are associated with complications of orbital adherence syndrome [14].…”
Section: Discussionmentioning
confidence: 99%
“…A fifth benefit of our present approach was that the template and the press were used together to maximize the molding effect. Previously, Callahan et al [4] and Fan et al [6] have also reported the use of orbital implant templates in orbital reconstructions. In both of these prior studies, the surgeon manually shaped and trimmed the implant on the templates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D printing and rapid prototyping have been used in ophthalmic plastic surgery for the correction of complex orbito-zygomatic fractures and in creation of PSIs for volume augmentation in the orbit. [ 28 29 30 ] 3D printing and computer-assisted techniques allow for the creation of patients’ orbit in vitro using freely available softwares such as CURA. This orbital model serves as a mould for fabrication of PSI.…”
Section: Discussionmentioning
confidence: 99%
“…presented five cases of orbital reconstructions with the aid of 3D-printed implant templates. [ 9 ] First, the shape of an orbital defect was measured based on the intact contralateral orbit as a standard Tessellation language file, and then, the mock implant was printed. After sterilization, they used the mock implant intraoperatively as a stencil and shaped on the actual implant.…”
Section: Discussionmentioning
confidence: 99%